Awareness, Behaviors and Perception regarding the COVID-19 Pandemic among Health Care Workers - Khurram Baqai, Mahvesh Mahmud, Atif Ahmed, Muhammad Ikram Ul Haq, Muhammad Afzal, Mian Mukhtar Ul Haq (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: It is essential that frontline forces like health care workers (HCWs) should have updated knowledge about the COVID-19 pandemic trends and its epidemiology. Objective: This study was conducted to make an assessment of the awareness, perceptions and behaviors of HCWs towards the recent pandemic of COVID-19. Methods: A cross-sectional survey on a structured questionnaire was carried out in a hospital in the metropolis of Karachi among HCWs involved in the management and treatment of COVID-19 from March to August 2023. A total of 179 responses from doctors, paramedical staff, laboratory technicians, nurses and other ground staff workers were received. Results: The majority of the respondents were males (110, 61%) and physicians (54%), with a total work experience of 5 years or more (70%). 5 percent were noted to have had a prior experience in treating patients during the outbreak. The survey revealed that the participants of the study had some knowledge about precautionary measures and the management of patients. However, many of the HCWs were not aware about current updates sample testing and on quarantine measures. It was perceived by many HCWs that this pandemic as a public health issue of great importance, and were also concerned about getting infected themselves. Conclusion: HCWs lack enough understanding about the COVID-19 pandemic, both in terms of epidemiology and current updates. As a result, regular updates must be provided through educational seminars that make use of virtual media, and professional counselors may be scheduled to help reduce anxiety related to the pandemic. Keywords: SARS-CoV-2, COVID-19, Health care workers (HCWs) le History.